2015
DOI: 10.2214/ajr.13.12435
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Insall-Salvati Ratios in Children With an Acute Anterior Cruciate Ligament Tear and a Matched Control Population

Abstract: There is a significant association between an ACL tear and increased patellar tendon length with a greater Insall-Salvati ratio. The mechanism for this finding is unclear, but this association provides support to suggest relative patella alta may be a risk factor for ACL injuries in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…As a result of another study that evaluated ACL injuries in children, there is a significant association between an ACL tear and the increased patellar tendon length with a greater Insall-Salvati ratio. For this reason, patella alta can be a risk factor for ACL injuries in pediatric patients [14]. Mean preoperative value of the Insall-Salvati ratio is 0.91 ± 0.1 according to our study.…”
Section: Discussionsupporting
confidence: 55%
“…As a result of another study that evaluated ACL injuries in children, there is a significant association between an ACL tear and the increased patellar tendon length with a greater Insall-Salvati ratio. For this reason, patella alta can be a risk factor for ACL injuries in pediatric patients [14]. Mean preoperative value of the Insall-Salvati ratio is 0.91 ± 0.1 according to our study.…”
Section: Discussionsupporting
confidence: 55%
“…Patella alta has also been implicated as a non-modifiable risk factor for ACL injuries in patients with open physes. This study demonstrated an association between ACL tear and increased patellar tendon length with a greater Insall-Salvati ratio [73].…”
Section: Risk Factors and Preventionsupporting
confidence: 50%
“… 5 In addition, patellofemoral (PF) instability is a clinical syndrome caused by morphological abnormalities in the PF joint and, it has been shown to interfere with knee extension and flexion, contributing to ACL damage. 6 , 18 …”
mentioning
confidence: 99%